2009
DOI: 10.4049/jimmunol.0803157
|View full text |Cite
|
Sign up to set email alerts
|

Menopause and Ovariectomy Cause a Low Grade of Systemic Inflammation that May Be Prevented by Chronic Treatment with Low Doses of Estrogen or Losartan

Abstract: The incidence of cardiovascular diseases in premenopausal women is lower than in men or postmenopausal women. This study reports the discovery of a low grade of systemic inflammation, including monocyte adhesion to arterial endothelium, elicited by menopause or estrogen depletion. Chronic treatment with low dose of 17-β-estradiol or inhibition of the renin-angiotensin system reduced this inflammation. Using an in vitro flow chamber system with human arterial and venous endothelial cells, we found that leukocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
103
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 142 publications
(107 citation statements)
references
References 52 publications
3
103
0
1
Order By: Relevance
“…Along this line, E2 has been shown to inhibit IL-1-dependent induction of membrane E-selectin, ICAM-1 and VCAM-1 on cultured endothelial cells [30][31][32]. Interestingly, using intravital microscopy, it has been recently shown that ovariectomy in rats resulted in enhanced monocyte adhesion to arterial endothelium that was associated with increased adhesion molecule expression [33]. Supplementation with low dose of E2 inhibited the ovariectomy-induced upregulation of adhesion molecule expression on endothelium and adhesiveness of leukocytes, suggesting that endogenous estrogens may act to downregulate low grade microvascular inflammation in vivo [33].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Along this line, E2 has been shown to inhibit IL-1-dependent induction of membrane E-selectin, ICAM-1 and VCAM-1 on cultured endothelial cells [30][31][32]. Interestingly, using intravital microscopy, it has been recently shown that ovariectomy in rats resulted in enhanced monocyte adhesion to arterial endothelium that was associated with increased adhesion molecule expression [33]. Supplementation with low dose of E2 inhibited the ovariectomy-induced upregulation of adhesion molecule expression on endothelium and adhesiveness of leukocytes, suggesting that endogenous estrogens may act to downregulate low grade microvascular inflammation in vivo [33].…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, using intravital microscopy, it has been recently shown that ovariectomy in rats resulted in enhanced monocyte adhesion to arterial endothelium that was associated with increased adhesion molecule expression [33]. Supplementation with low dose of E2 inhibited the ovariectomy-induced upregulation of adhesion molecule expression on endothelium and adhesiveness of leukocytes, suggesting that endogenous estrogens may act to downregulate low grade microvascular inflammation in vivo [33]. The effect of estrogens on immune response and on the physiopathology of autoimmune diseases is complex and paradoxical [1].…”
Section: Discussionmentioning
confidence: 99%
“…HUAEC were isolated from arteries from freshly human umbilical cords, as previously described (Abu-Taha et al, 2009). Briefly, both umbilical arteries were isolated, cannulated, their interior washed with PBS and then incubated 15 min with a 0.2% type II collagenase solution (Invitrogen, Barcelona, Spain).…”
Section: Cell Culture and Experimental Designmentioning
confidence: 99%
“…In addition to regulating the components involved in synthesizing Ang-II, estrogens also alter the expression of Ang-II AT 1 receptors in many target tissues (20,21). In this context, we have encountered an increase in leukocyte adhesion to the arterial endothelium, CAM expression, and circulating chemokine levels in ovariectomized (OVZ) rats without parallel changes in arterial blood pressure (22), indicating that estrogen deficiency results in a low grade of systemic inflammation. Furthermore, chronic administration of low doses of estradiol or inhibition of the rennin-angiotensin system immediately after ovariectomy dramatically reduced this inflammatory state (22).…”
mentioning
confidence: 99%
“…In this context, we have encountered an increase in leukocyte adhesion to the arterial endothelium, CAM expression, and circulating chemokine levels in ovariectomized (OVZ) rats without parallel changes in arterial blood pressure (22), indicating that estrogen deficiency results in a low grade of systemic inflammation. Furthermore, chronic administration of low doses of estradiol or inhibition of the rennin-angiotensin system immediately after ovariectomy dramatically reduced this inflammatory state (22). HRT is no longer prescribed, and so new and safer drugs that ameliorate the systemic inflammation that is characteristic of the menopause are essential.…”
mentioning
confidence: 99%